Altered expression and mutations in cell cycle genes CCND1, CDK4, CDKN2B and TP53 are associated with Pakistani breast cancer patients - Wajeeha Tariq; Ali Raza Awan; Asim Khalid Mahmood; Muhammad Wasim (Molecular Biology Reports, 2026)

AM fungal and rhizobacteria jointly enhance vegetable waste decomposition in soils and harvest environmental and agronomic benefits in dryland - Muhammad Maqsood Ur Rehman; Sidra Khattak; Ling Zhao; Yun-Li Xiao; Ying Zhu; Awais Iqbal; Rafi Ullah; Nang Chang; Muhammad Abrar; Jian-Ming Li; Hao Sun; Adnan Khan; et al. (Agriculture, Ecosystems & Environment, 2026)

Assessing the influence of different post-harvest dormancy-breaking methods on the physicochemical characteristics of potato - Syed Mohsin Abbas; Raina Ijaz; Tanveer Hussain; Muhammad Nafees; Muhammad Wasim Haider; Alina-Stefania Stanciu; Ulkar İbrahimova (Postharvest Biology and Technology, 2026)

Gastrodia elata Blume (Tianma) extract mitigates simulated microgravity–induced oxidative stress and enhance learning and memory in Caenorhabditis elegans - Muhammad Zulqarnain Shakir; Inam Ullah; Muhammad Wasim Usmani; Jiang Ning; Jixian Liu; Xuchen Zhou; Yufen Zhao; Guanghua Lu; Qiaobei Du; Huabiao Chen; Muhammad Imran; Muhammad Ashraf; et al. (Life Sciences in Space Research, 2026)

Germination-driven biochemical remodeling of cereals and pseudocereals: Impacts on nutrient bioaccessibility, phytochemical enrichment, and functional food potential - Djilali Benabdelmoumene; Muhammad Waqar; Abderahman Shawky; Omnia Darwish Askar; Wasim S.M. Qadi; Said Dahmouni; Mariam Gamaleldin; Faidruz Azura Jam; Ahmed Mediani; Hamizah Shahirah Hamezah; Habsah Aziz; Sajad Ali; et al. (Food Chemistry, 2026)

Retraction notice to “The asymmetric nexus between air pollution and COVID-19: Evidence from a non-linear panel autoregressive distributed lag model” [Environ. Res. 209 (2022) 112848] - Chen Wen; Rabia Akram; Muhammad Irfan; Wasim Iqbal; Vishal Dagar; Ángel Acevedo-Duqued; Hayot Berk Saydaliev (Environmental Research, 2026)

Effects of yeast β-glucan on the digestibility of extruded corn starch with varying amylose contents - Manman Lu; Haoyuan Wang; Zhilong Zeng; Ahmed H. Abdullah; Yijia Li; Muhammad Wasim; Min Zhou; Xiong Liu (Food Bioscience, 2026)

The Influence of Policy Indicators on Circular Economy Metrics in Australia: Application of Asymmetric Analysis - Suleman Sarwar; Afifa Qadeer; Rida Waheed; Ghazala Aziz; Muhammad Wasim Hussan (Circular Economy and Sustainability, 2026)

Neurobiological and neurophysiological impacts of real spaceflight and simulated microgravity on C. elegans: a comprehensive review - Muhammad Zulqarnain Shakir; Ning Wang; Muhammad Wasim Usmani; Inam Ullah; Jixian Liu; Xuchen Zhou; Yufen Zhao; Qiaobei Du; Huabiao Chen; Jiang Ning; Xinmin Liu (Life Sciences in Space Research, 2026)

Antibiotic resistance pattern and molecular study of foodborne pathogenic bacteria isolated from Poultry meat in Bangladesh - Shahin Mahmud; Muhammad Wasim; Md. Firoz Ali; Md. Omar Faruque; Sourav Sarker; Md. Rayhan Ali; Ashraf Hossain Talukder; A.K.M. Mohiuddin; Somaresh Kumar Mondal; Shah Adil Ishtiyaq Ahmad (Food and Humanity, 2026)

Retraction Note: Optimizing callogenesis in five potential medicinal herbs for the bioactive constituents: a sustainable approach to pharmaceutical production - Muhammad Wasim Haider; Muhammad Nafees; Maryyam Bint-e-Tariq; Umar Farooq; Tanveer Hussain; Taki Demir; Asad Masood; Muhammad Samsam Raza; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Ozhan Simsek; Temoor Ahmed; et al. (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Nexus between agro-ecological efficiency and carbon emission transfer: evidence from China - Usman Akbar; Quan-Lin Li; Muhammad Abdullah Akmal; Mohammed Shakib; Wasim Iqbal (Environmental Science and Pollution Research, 2026)

Retraction Note: Trilemma assessment of energy intensity, efficiency, and environmental index: evidence from BRICS countries - Zulifqar Ali Baloch; Qingmei Tan; Nadeem Iqbal; Muhammad Mohsin; Qaiser Abbas; Wasim Iqbal; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2026)

Retraction Note: Environmental efficiency and the role of energy innovation in emissions reduction - Muhammad Khalid Anser; Wasim Iqbal; Umar Suffian Ahmad; Arooj Fatima; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2026)

Cereal-legume intercropping stabilizes yield and economic advantages under variable rainfall in semiarid rainfed environment - Wei Wang; Bao-Zhong Wang; Wei Zhang; Meng-Ying Li; Jian-Ming Li; Sheng-Jun Ji; Muhammad Abrar; Muhammad Maqsood Ur Rehman; Wasim Khan; Hong-Yan Tao; Mohamed S. Sheteiwy; Wen-Ying Wang; et al. (European Journal of Agronomy, 2026)

Effect of Hong Huang Tang on memory enhancement and mitigation of microgravity-induced oxidative stress in C. elegans - Inam Ullah; Muhammad Zulqarnain Shakir; Xu Chen Zhou; Jixian Liu; Shilan Li; Huabiao Chen; Ning Jiang; Muhammad Wasim Usmani; Muhammad Qasim Barkat; Qiaobei Du; Yufen Zhao; Ning Wang; et al. (Biogerontology, 2026)

Mechanistic insights into the synergistic pharmacology of quercetin–kaempferol against SARS-CoV-2 infection - Farman Ali; Muhammad Zubair Saleem; Muhammad Mohsin; Saleem Ahmad; Waqar Islam; Wasim Qasim; Muhammad Tayyab (In Silico Pharmacology, 2026)

Synergistic effects of biochar and silicon dioxide nanoparticles abate cadmium uptake and oxidative stress in tomato: Achieving crop resilience and environmental sustainability - Muhammad Kashif Irshad; Muhammad Waseem; Saba Saleem; Jamilur R. Ansari; Sana Ashraf; Wasim Javed; Ali Noman; Muhammad Aqeel; Muhammad Rizwan; Afrah E. Mohammed; Modhi O. Alotaibi; Muhammad Rizwan; et al. (Plant Science, 2026)

Biochar and plant growth-promoting rhizobacteria: a promising combination enhancing wheat (Triticum aestivum L.) growth under chromium stress - Fazal Jalal; Awais Ahmad; Aqib Iqbal; Zafar Hayat Khan; Shah Fahad; Nazia Tahir; Fazal Said; Muhammad Imtiaz; Muhammad Ali Khan; Sayed Hussain; Attaur Rahman; Wasim Khan; et al. (Rhizosphere, 2025)

Biphasic synthesis of Pd/Ovs-TiO₂ (black) for efficient moxifloxacin degradation and toxicity mitigation - Muhammad Imran Kanjal; Iram Yasmin; Syed Kashif Ali; Muhammad Wasim Afzal; Muhammad Irfan Ahamad; Mohamed A. Habib; Ahmed B.M. Ibrahim; Rana Muhammad Zulqarnain (Journal of Water Process Engineering, 2025)

Genotoxic and oxidative stress assessment of heavy metal contaminated soil and water in human blood and bovine milk samples from the different industrial zones of Punjab, Pakistan - Muhammad Muddassir Ali; Furqan Awan; Muhammad Usman Jamil; Muhammad Ijaz; Asad Ullah; Wasim Shehzad (Journal of Trace Elements in Medicine and Biology, 2025)

Electrochemical CO2 reduction: Converting greenhouse gas into high-value products for a sustainable future - Muhammad Wasim Afzal; Muhammad Imran Kanjal; RuiFeng Ren; Shazia Ashraf; Syed Rizwan Shafqat; Jiang Shao; Lutong Wang; Ma Jingye; Xue Liu; Yan Bai; Dongbin Dang (Journal of Environmental Chemical Engineering, 2025)

Exploration of medicinal and nutritional value of Himalayan wild edible fruits: implications for sustainable health and functional foods - Syeda Khateeb Fatima; Rizwan Taj Khan; Munazza Nazir; Muhammad Manzoor; Syed Waseem Gillani; Mumna Munir; Muhammad Nasir; Wasim Akhtar; Shabir Ahmad; Manal Abdulaziz Binobead; M Ajmal Ali (Genetic Resources and Crop Evolution, 2025)

Microfacies analysis and depositional environment of Eocene Chorgali formation at Khanpur Dam Road Section, Hazara Basin, Pakistan - Bilal Shah; Syed Mamoon Siyar; Salman Khurshid; Dicky Muslim; Raden Irvan Sophian; Zahid Ullah; Abdul Wahid Asykarulloh; Asad Muhammad; Syed Muhammad; Wasim Sajjad (Carbonates and Evaporites, 2025)

Amplification effects of AM fungus and rhizobacteria on carbon efficiency in wheat-soil system under drought stress via priming rhizosphere activities - Muhammad Maqsood Ur Rehman; Ling Zhao; Sidra Khattak; Yun-Li Xiao; Awais Iqbal; Wasim Khan; Muhammad Abrar; Zheng-Guo Cheng; Shi-Sheng Li; Asfa Batool; Ying Zhu; You-Cai Xiong (Applied Soil Ecology, 2025)

Optimizing the anticancer action and toxicity evaluation of cobalt ferrite nanoparticles by different polyethylene glycol concentrations - Kanwal Akhtar; Muhammad Khawar Abbas; Nida Muzammil; Naveed Akhtar Shad; Qaisar Iqbal; Wasim Abbas; Faqir Muhammad; Bushra Akhtar; Yasir Javed; Habiba Khadim; Anam Munawar (Journal of Trace Elements in Medicine and Biology, 2025)

GC-MS profiling and biological investigations of Cissampelos pareira L. & Lantana camara L. - Muhammad Wasim; Hafiz Abdul Rafey; Sadia Sarwar; Humaira Nadeem; Samir Anis Ross; Farhat Shaheen (Natural Product Research, 2025)

Boosted wound healing and anticancer potential of polymer functionalized cerium oxide nanomaterials - Muhammad Khawar Abbas; Yasir Javed; Naveed Akhtar Shad; Azhar Rasul; Amna Bashir; Syed Fazil Bin Farukh; Heba Taha Abdulghani; Wasim Abbas; Aisha Sethi; Muhammad Ramzan Khawar; Dongwhi Choi (Journal of Trace Elements in Medicine and Biology, 2025)

Genetic analysis in a consanguineous MCPH family revealed a refinement of the MCPH12 locus and a founder effect of the recurrent CDK6 variant [c.589G>A, p.(Ala197Thr)] in the Pakistani population - Muzammil Ahmad Khan; Jasmin Blatterer; Markus Kuster; Lukas Kaufmann; Peter M. Kroisel; John B. Vincent; Muhammad Zubair; Muhammad Muzammal; Nisar Ahmad; Shakil Abbas; Wasim Shah; Muhammad Zeeshan Ali; et al. (Journal of Genetics, 2025)

Stage-dependent synergistic impacts of AM fungi and rhizobacteria on phytohormone mediation and field productivity in dryland maize - Muhammad Abrar; Ying Zhu; Wen-Shan Li; Muhammad Aqeel; Umair Ashraf; Muhammad Maqsood Ur Rehman; Jian-Ming Li; Xiao-Fang Gong; Wasim Khan; Wei Wang; You-Cai Xiong (Field Crops Research, 2025)

Effects of enzyme supplementation and fermentation in canola-based diets on growth performance, intestinal viscosity and histomorphology in broiler chickens during the finisher phase - Wasim Akram; Abdul Hafeez; Sarzamin Khan; Muhammad Tahir; Rifat Ullah Khan (Tropical Animal Health and Production, 2025)

Exploring Proteomic Alterations in Intellectual Disability: Insights from Hyperlipidemia and Hyperphosphatasia Subgroups - Soma Vankwani; Munazza Raza Mirza; Muhammad Tahir; Muhammad Wasim; Sajid Ali Rajput; Haq Nawaz Khan; Martin R. Larsen; Muhammad Iqbal Choudhary; Fazli Rabbi Awan (NeuroMolecular Medicine, 2025)

Evaluation of genotoxicity and physicochemical variations of Eichhornia crassipes (Mart.) Solms exposed to paper-mill-contaminated wastewater - Harma Shah; Muhammad U. F. Awan; Zahid Mehmood; Noor Sana; Wasim Abbas; Adeel Ahmad; Abdullah Qasim; Annum Gul; Ali Hasnain; Hsi-Hsien Yang (Environmental Monitoring and Assessment, 2025)

Textile wastewater treatment by heterogeneous catalytic ozonation using microcellulose loaded ZIF 67 catalyst - Muhammad Fahad Tariq; Farhan Javed; Luigi Rizzo; Muhammad Wasim Tahir; Amir Ikhlaq (Journal of Environmental Management, 2025)

RETRACTED ARTICLE: Optimizing callogenesis in five potential medicinal herbs for the bioactive constituents: a sustainable approach to pharmaceutical production - Muhammad Wasim Haider; Muhammad Nafees; Maryyam Bint-e-Tariq; Umar Farooq; Tanveer Hussain; Taki Demir; Asad Masood; Muhammad Samsam Raza; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Ozhan Simsek; Temoor Ahmed; et al. (Genetic Resources and Crop Evolution, 2025)

Isolation and characterization of ureolytic calcifying bacteria from methane hydrate-bearing marine sediments for bio-cementation application - Sahib Zada; Muhammad Rafiq; Wasim Sajjad; Muhammad Afzal; Zheng Su; Liu Lihua (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Towards a green economy: Investigating the impact of sustainable finance, green technologies, and environmental policies on environmental degradation - Muhammad Ahsan Iqbal; Wasim Abbas Shaheen; Suheela Shabir; Usman Ullah; Ienciu Ionel-Alin; Marius-Ioan Mihut; António Raposo; Heesup Han (Journal of Environmental Management, 2025)

Reshaping the healthcare world by AI-integrated wearable sensors following COVID-19 - Bangul Khan; Rana Talha Khalid; Khair Ul Wara; Muhammad Hasan Masrur; Samiullah Khan; Wasim Ullah Khan; Umay Amara; Saad Abdullah (Chemical Engineering Journal, 2025)

RbcLa marker based identification and phylogenetic analysis of Kasuri methi (Trigonella foenum-graecum L.): a native plant of Kasur district of Punjab (Pakistan) - Bin Yameen; Wasim Abbas; Muhammad Umer Farooq Awan; Aisha Tahir; Sohaib Mohammad; Muhammad Shoib (Genetic Resources and Crop Evolution, 2025)

Potential of iron oxide-modified biochar in simultaneous mitigation of lead and nickel toxicity in wheat (Triticum aestivum L.) - Tufail Shah; Muhammad Kashif Irshad; Wasim Javed; Mahshab Sheraz; Atif Muhmood; Ali Noman; Maryam M. Alomran; Sang Soo Lee; Jianying Shang (South African Journal of Botany, 2024)

Mechanistic insight into interactive effect of microplastics and arsenic on growth of rice (Oryza sativa L.) and soil health indicators - Muhammad Kashif Irshad; Muhammad Aqeel; Saba Saleem; Wasim Javed; Ali Noman; Min Woo Kang; Noreen Khalid; Sang Soo Lee (Science of The Total Environment, 2024)

Successful application of modified crude DNA extraction from muscle tissues for various types of PCR amplifications - Sana Jafar; Salman Jamil; Muhammad Sheraz Yasin; Asif Naseem; Muhammad Yasir Zahoor; Wasim Shehzad; Muhammad Imran (Molecular Biology Reports, 2024)

The interplay of PTEN and AKT nexus in breast cancer: a molecular perspective - Anum Kamal; Ali Raza Awan; Masood Rabbani; Hammad Raza Sheikh; Muhammad Tayyab; Sehrish Firyal; Imran H. Khan; Muhammad Wasim (Molecular Biology Reports, 2024)

Development and validation of a universal primer pair for the taxonomic and phylogenetic studies of vertebrates - Sana Jafar; Khalid Mahmood Anjum; Muhammad Yasir Zahoor; Wasim Shehzad; Asif Naseem; Muhammad Imran (Molecular Biology Reports, 2024)

A novel homozygous missense TTC12 variant identified in an infertile Pakistani man with severe oligoasthenoteratozoospermia and primary ciliary dyskinesia - Imtiaz Ali; Haider Ali; Ahsanullah Unar; Fazal Rahim; Khalid Khan; Sobia Dil; Tanveer Abbas; Ansar Hussain; Aurang Zeb; Muhammad Zubair; Huan Zhang; Hui Ma; et al. (Molecular Genetics and Genomics, 2024)

Sedimentology, diagenesis and sequence stratigraphy of the Early–Middle Eocene Chorgali Formation in the Hazara sub-Basin, Northwest Himalayas, Pakistan - Emad Ullah Khan; Shadab Khan; Syed Muhammad Wasim Sajjad; Maryam Saleem; Muhammad Ilyas; Saif Ullah Khan (Carbonates and Evaporites, 2024)

Sequence variants underlying severe combined immunodeficiency and leukocyte adhesion deficiency type 1 in six consanguineous families - Hajra Fayyaz; Atteaya Zaman; Nighat Haider; Rehmana Waris; Muhammad Hussain; Syed Irfan Raza; Wasim Ahmad; Imran Ullah (Immunogenetics, 2024)

Retraction Note: The dynamics of public spending on sustainable green economy: role of technological innovation and industrial structure effects - Hou Yumei; Wasim Iqbal; Muhammad Irfan; Arooj Fatima (Environmental Science and Pollution Research, 2024)

Retraction Note: Assessing the nexus between COVID-19 pandemic–driven economic crisis and economic policy: lesson learned and challenges - Lei Chang; Muhammad Mohsin; Wasim Iqbal (Environmental Science and Pollution Research, 2024)

Retraction Note: Assessing the performance of sustainable entrepreneurship and environmental corporate social responsibility: revisited environmental nexus from business firms - Zafran Ahmad; Liu Chao; Wang Chao; Wasim Iqbal; Sulaman Muhammad; Shujaat Ahmed (Environmental Science and Pollution Research, 2024)

Efficacy of Fe-Mg-bimetallic biochar in stabilization of multiple heavy metals-contaminated soil and attenuation of toxicity in spinach (Spinacia oleracea L.) - Muhammad Kashif Irshad; Jong Cheol Lee; Muhammad Aqeel; Wasim Javed; Ali Noman; Su Shiung Lam; Ali El Naggar; Nabeel Khan Niazi; Hun Ho Lee; Muhammad Ibrahim; Sang Soo Lee (Chemosphere, 2024)

The limits to equity in water allocation under scarcity - Wasim Hassan; Talha Manzoor; Abubakr Muhammad (Journal of Hydrology, 2024)

Retraction Note: Nexus between energy policy and environmental performance in China: The moderating role of green finance adopted firms - Muhammad Ghazanfar Abbas; Zhuquan Wang; Shahid Bashir; Wasim Iqbal; Hafeez Ullah (Environmental Science and Pollution Research, 2024)

Retraction Note: COVID-19 and stock exchange return variation: empirical evidences from econometric estimation - Yousaf Latif; Ge Shunqi; Shahid Bashir; Wasim Iqbal; Salman Ali; Muhammad Ramzan (Environmental Science and Pollution Research, 2024)

Evaluating the relative influence of climate and human activities on recent vegetation dynamics in West Bengal, India - Abhishek Banerjee; Shichang Kang; Michael E. Meadows; Wasim Sajjad; Ali Bahadur; Muhammad Farhan Ul Moazzam; Zilong Xia; Joseph Mango; Bappa Das; Kelly L. Kirsten (Environmental Research, 2024)

Label free quantitative proteomic profiling of serum samples of intellectually disabled young patients revealed dysregulation of complement coagulation and cholesterol cascade systems - Soma Vankwani; Munazza Raza Mirza; Fazli Rabbi Awan; Muneeza Zafar; Arkadiusz Nawrocki; Muhammad Wasim; Haq Nawaz Khan; Hina Ayesha; Martin Rossel Larsen; Muhammad Iqbal Choudhary (Metabolic Brain Disease, 2024)

Unveiling the detrimental effects of polylactic acid microplastics on rice seedlings and soil health - Muhammad Kashif Irshad; Min Woo Kang; Muhammad Aqeel; Wasim Javed; Ali Noman; Noreen Khalid; Sang Soo Lee (Chemosphere, 2024)

Temperature-dependent transformation of microbial community: A systematic approach to analyzing functional microbes and biogas production - Ali Bahadur; Lu Zhang; Wei Guo; Wasim Sajjad; Nikhat Ilahi; Abhishek Banerjee; Shah Faisal; Muhammad Usman; Tuo Chen; Wei Zhang (Environmental Research, 2024)

Impact of sustainable practices on knowledge sharing, relationship commitment, and sustainable performance - Muzzammil Wasim Syed; Huaming Song; Muhammad Junaid (Environment, Development and Sustainability, 2024)

Recent advances in recognition molecule-based detection methods for prevention and monitoring of estrogen disruptors related food fraud - Zhen Zhang; Ruiping Shan; Wasim Tasleem Muhammad; Hongyan Zhang (Trends in Food Science & Technology, 2024)

Bacteria populating freshly appeared supraglacial lake possess metals and antibiotic-resistant genes - Wasim Sajjad; Nikhat Ilahi; Abdul Haq; Zhanhuan Shang; Ghulam Nabi; Muhammad Rafiq; Ali Bahadur; Abhishek Banerjee; Shichang Kang (Environmental Research, 2024)

Cryosphere: a frozen home of microbes and a potential source for drug discovery - Sahib Zada; Mohsin Khan; Zheng Su; Wasim Sajjad; Muhammad Rafiq (Archives of Microbiology, 2024)

Pathways to ecological resilience: exploring green energy and finance for sustainable development - Iqra Mehroush; Wasim Abbas Shaheen; Mohsin Shabir; Muhammad Talha (Environment, Development and Sustainability, 2024)

Temperature drives microbial communities in anaerobic digestion during biogas production from food waste - Tuo Chen; Lu Zhang; Wei Guo; Wei Zhang; Wasim Sajjad; Nikhat Ilahi; Muhammad Usman; Shah Faisal; Ali Bahadur (Environmental Science and Pollution Research, 2024)

Above-and below-ground feedback loop of maize is jointly enhanced by plant growth-promoting rhizobacteria and arbuscular mycorrhizal fungi in drier soil - Wasim Khan; Ying Zhu; Aziz Khan; Ling Zhao; Yu-Miao Yang; Ning Wang; Meng Hao; Yue Ma; Jaya Nepal; Fazal Ullah; Muhammad Maqsood Ur Rehman; Muhammad Abrar; et al. (Science of The Total Environment, 2024)

Microbial diversity and community structure dynamics in acid mine drainage: Acidic fire with dissolved heavy metals - Wasim Sajjad; Nikhat Ilahi; Shichang Kang; Ali Bahadur; Abhishek Banerjee; Sahib Zada; Barkat Ali; Muhammad Rafiq; Guodong Zheng (Science of The Total Environment, 2024)

Patterns of bacterial communities in the rhizosphere and rhizoplane of alpine wet meadows - Awais Iqbal; Muhammad Maqsood Ur Rehman; Wasim Sajjad; Abraham Allan Degen; Muhammad Rafiq; Niu Jiahuan; Salman Khan; Zhanhuan Shang (Environmental Research, 2024)

Advancements in technology and innovation for sustainable agriculture: Understanding and mitigating greenhouse gas emissions from agricultural soils - Muhammad Qayyum; Yanping Zhang; Mansi Wang; Yuyuan Yu; Shijie Li; Wasim Ahmad; Saleh N. Maodaa; Shaban R.M. Sayed; Jiawei Gan (Journal of Environmental Management, 2023)

High prevalence of antibiotic-resistant and metal-tolerant cultivable bacteria in remote glacier environment - Wasim Sajjad; Barkat Ali; Hewen Niu; Nikhat Ilahi; Muhammad Rafiq; Ali Bahadur; Abhishek Banerjee; Shichang Kang (Environmental Research, 2023)

Sequence variants in different genes underlying Bardet-Biedl syndrome in four consanguineous families - Amjad Ali; Abdullah; Muhammad Bilal; Emily Kathryn Mis; Saquib Ali Lakhani; Wasim Ahmad; Imran Ullah (Molecular Biology Reports, 2023)

Unlocking therapeutic potential of trigonelline through molecular docking as a promising approach for treating diverse neurological disorders - Syeda Rehana Zia; Muhammad Wasim; Saara Ahmad (Metabolic Brain Disease, 2023)

Risk assessment of toxic and hazardous metals in paddy agroecosystem by biochar-for bio-membrane applications - Muhammad Kashif Irshad; Sihang Zhu; Wasim Javed; Jong Cheol Lee; Abid Mahmood; Sang Soo Lee; Shang Jianying; Gadah Albasher; Atif Ali (Chemosphere, 2023)

Emerging trends of green hydrogen and sustainable environment in the case of Australia - Afifa Qadeer; Muhammad Wasim Hussan; Ghazala Aziz; Rida Waheed; Suleman Sarwar (Environmental Science and Pollution Research, 2023)

Strength Mechanism of a Swelling Soil Improved with Jute Fibers: A Laboratory Treatment - Muhammad Wasim Tariq; Jahanzaib Israr; Khalid Farooq; Hassan Mujtaba (Geotechnical and Geological Engineering, 2023)

Observing the response of environmental and economic performances to tourism in light of structural changes - Muhammad Wasim Akram; Shuchun Yang; Muhammad Hafeez (Air Quality, Atmosphere & Health, 2023)

Eco-innovation and environmental entrepreneurship: steps towards business growth - Muhammad Wasim Akram; Shuchun Yang; Muhammad Hafeez; Md. Abdul Kaium; Israt Zahan; Raufhon Salahodjaev (Environmental Science and Pollution Research, 2023)

Asian logistics industry efficiency under low carbon environment: policy implications for sustainable development - Muhammad Wasim Akram; Muhammad Hafeez; Shuchun Yang; Narayan Sethi; Shaza Mahar; Raufhon Salahodjaev (Environmental Science and Pollution Research, 2023)

A novel S-type CsxWO3/BiOI heterojunction photocatalyst constructed in graphene aerogel with high degradation efficiency for enrofloxacin: Degradation mechanism and DFT calculation - Tianci Li; Jingxiao Liu; Fei Shi; Haoyuan Zhang; Haojie Zhang; Chuangchuang Ma; Muhammad Wasim (Journal of Environmental Chemical Engineering, 2023)

Description of novel variants in consanguineous Pakistani families affected with intellectual disability - Iqra Ghulam Rasool; Muhammad Yasir Zahoor; Irfan Ahmed; Muhammad Iqbal; Shehla Shafqat; Aftab Ahmad Anjum; Wasim Shehzad (Genes & Genomics, 2023)

Determinants of CSR and green purchase intention: Mediating role of customer green psychology during COVID-19 pandemic - Wasim Ahmad; Rana Muhammad Sohail Jafar; Abdul Waheed; Huaping Sun; Sayed Sibtain Ali Shah Kazmi (Journal of Cleaner Production, 2023)

Natural remedies for Alzheimer’s disease: A systematic review of randomized controlled trials - Saara Ahmad; Saad Bilal Ahmed; Asra Khan; Muhammad Wasim; Saiqa Tabassum; Saida Haider; Fatima Ahmed; Zehra Batool; Saima Khaliq; Hamna Rafiq; Prashant Tikmani; Anwar-ul-Hassan Gilani (Metabolic Brain Disease, 2023)

How do financial fragility and ICT penetration affect renewable energy consumption and green growth in top-polluting economies? - Muhammad Wasim Akram; Danish Ahmed; Anna Trunina; Kashif Hamid; Muhammad Hafeez (Environmental Science and Pollution Research, 2022)

Determining the most effective way of intervention in forest fires with fuzzy logic modeling : the case of Antalya/Türkiye - Ahmet Şahiner; Temel Ermiş; Mete Hakan Karakoyun; Muhammad Wasim Awan (Natural Hazards, 2022)

How do energy prices and climate shocks affect human health? Insights from BRICS - Wenxin Wang; Muhammad Hafeez; Hong Jiang; Muhammad Usman Ashraf; Muhammad Asif; Muhammad Wasim Akram (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Assessing the nexus between COVID-19 pandemic–driven economic crisis and economic policy: lesson learned and challenges - Lei Chang; Muhammad Mohsin; Wasim Iqbal (Environmental Science and Pollution Research, 2022)

Moisture- and period-dependent interactive effects of plant growth-promoting rhizobacteria and AM fungus on water use and yield formation in dryland wheat - Muhammad Maqsood Ur Rehman; Ying Zhu; Muhammad Abrar; Wasim Khan; Wei Wang; Awais Iqbal; Anum Khan; Yuan Chen; Muhammad Rafiq; Muhammad Aammar Tufail; Jian-Sheng Ye; You-Cai Xiong (Plant and Soil, 2022)

Effect of economic development, income inequality, transportation, and environmental expenditures on transport emissions: evidence from OECD countries - Zahid Hussain; Muhammad Kaleem Khan; Wasim Abbass Shaheen (Environmental Science and Pollution Research, 2022)
Environmental quality has been pondered as an essential aspect of sustainable development across the global economies. Several factors such as economic development, income inequality, transportation, and environmental expenditures drastically influence environmental quality. More specifically, the transport sector is a major contributor to carbon emissions which deteriorate the environmental quality. Therefore, this study investigates whether economic development, transportation, environmental expenditures, and income inequality affect transport-carbon emissions for the OECD countries. Furthermore, panel time-series data period from 2000 to 2020 and cross-sectional autoregressive distributed lag method are used for transport-oriented environmental examination. Results demonstrate that transportation upsurges transport-carbon emission level by 46.45% on average. Moreover, the joint effect of economic development and environmental taxes significantly reduces transport-carbon emissions by 14.70%. Findings further suggest that an inverted U -shaped relationship exists between economic development and transport emission. Besides, income inequality, environmental expenditures, and green transportation are negatively associated with the coefficient of transport-carbon emissions. More interestingly, income inequality is negatively correlated with transport-carbon emissions across the sample countries. Furthermore, the joint effect of income inequality and economic development increases the emission level released by the transport sector. Thus, this research recommends some policies: countries should control traffic movements and increase environmental expenditures, and produce green transport vehicles to tackle environmental issues.

Phosphate solubilizing epilithic and endolithic bacteria isolated from clastic sedimentary rocks, Murree lower Himalaya, Pakistan - Imran Khan; Sahib Zada; Muhammad Rafiq; Wasim Sajjad; Sumayya Zaman; Fariha Hasan (Archives of Microbiology, 2022)

RETRACTED ARTICLE: The dynamics of public spending on sustainable green economy: role of technological innovation and industrial structure effects - Hou Yumei; Wasim Iqbal; Muhammad Irfan; Arooj Fatima (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Assessing the performance of sustainable entrepreneurship and environmental corporate social responsibility: revisited environmental nexus from business firms - Zafran Ahmad; Liu Chao; Wang Chao; Wasim Iqbal; Sulaman Muhammad; Shujaat Ahmed (Environmental Science and Pollution Research, 2022)

Comparative seismic performance assessment of RC and RC/ECC hybrid frame structures: a shake table study - Fasih Ahmed Khan; Muhammad Rashid; Sajjad Wali Khan; Muhammad Rizwan; Yasir Irfan Badrashi; Muhammad Fahim; Muhammad Ashraf Tanoli; Wasim Khaliq; Akhtar Gul (Innovative Infrastructure Solutions, 2022)

RETRACTED ARTICLE: Nexus between energy policy and environmental performance in China: The moderating role of green finance adopted firms - Muhammad Ghazanfar Abbas; Zhuquan Wang; Shahid Bashir; Wasim Iqbal; Hafeez Ullah (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: COVID-19 and stock exchange return variation: empirical evidences from econometric estimation - Yousaf Latif; Ge Shunqi; Shahid Bashir; Wasim Iqbal; Salman Ali; Muhammad Ramzan (Environmental Science and Pollution Research, 2021)

Population structure and phylogenetic relationship of Peach [Prunus persica (L.) Batsch] and Nectarine [Prunus persica var. nucipersica (L.) C.K. Schneid.] based on retrotransposon markers - Hina Naeem; Faisal Saeed Awan; Peter Michael Dracatos; Muhammad Wasim Sajid; Shahzad Saleem; Qudsia Yousafi; Muhammad Saad Khan; Asim Mehmood; Bushra Zulfiqar (Genetic Resources and Crop Evolution, 2021)

Low temperature and hypoxic conditions induce flavonoids biosynthesis and enhances antioxidant potential of crabapple (Malus profusion) fruits - Rana Naveed Ur Rehman; Sajid Ali; Mahmood Ul Hasan; Raheel Anwar; Muhammad Wasim Haider; Ahmad Sattar Khan; Aman Ullah Malik; Li Pengmin (Acta Physiologiae Plantarum, 2021)

Correction to: Nexus between agro-ecological efficiency and carbon emission transfer: evidence from China - Usman Akbar; Quan-Lin Li; Muhammad Abdullah Akmal; Mohammed Shakib; Wasim Iqbal (Environmental Science and Pollution Research, 2021)

Epidemiology of molecular probes in Xpert MTB/RIF assay in Khyber Pakhtunkhwa, Pakistan - Anwar Sheed Khan; Muhammad Tahir Khan; Sajid Ali; Taj Ali Khan; Muhammad Qasim; Arif Malik; Sajid Ali; Wasim Sajjad; Qurrat ul ain; Muhammad Irfan (Archives of Microbiology, 2021)

Influence of rainfall infiltration on the stability of unsaturated coal gangue accumulated slope - Kaleem Ullah Jan Khan; Chang-ming Wang; Muhammad Wasim Jan Khan; Zhu Liang; Shuo Li; Bai-long Li (Journal of Mountain Science, 2021)

Whole exome sequencing revealed novel variants in consanguineous Pakistani families with intellectual disability - Iqra Ghulam Rasool; Muhammad Yasir Zahoor; Muhammad Iqbal; Aftab Ahmad Anjum; Fatima Ashraf; Hafiz Qamar Abbas; Hafiz Muhammad Azhar Baig; Tariq Mahmood; Wasim Shehzad (Genes & Genomics, 2021)

RETRACTED ARTICLE: Nexus between agro-ecological efficiency and carbon emission transfer: evidence from China - Usman Akbar; Quan-Lin Li; Muhammad Abdullah Akmal; Mohammed Shakib; Wasim Iqbal (Environmental Science and Pollution Research, 2021)

Correction to: In Silico Evaluation of Food Derived Bioactive Peptides as Inhibitors of Angiotensin Converting Enzyme (ACE) - Qudsia Yousafi; Jannat Batool; Muhammad Saad Khan; Tamsila Perveen; Muhammad Wasim Sajid; Abrar Hussain; Asim Mehmood; Shahzad Saleem (International Journal of Peptide Research and Therapeutics, 2021)

In Silico Evaluation of Food Derived Bioactive Peptides as Inhibitors of Angiotensin Converting Enzyme (ACE) - Qudsia Yousafi; Jannat Batool; Muhammad Saad Khan; Tamsila Perveen; Muhammad Wasim Sajid; Abrar Hussain; Asim Mehmood; Shahzad Saleem (International Journal of Peptide Research and Therapeutics, 2021)

Fluoride and arsenic contamination in drinking water due to mining activities and its impact on local area population - Tasawar Ali Chandio; Muhammad Nasiruddin Khan; Maria Taj Muhammad; Ozcan Yalcinkaya; Agha Arslan Wasim; Ahmet Furkan Kayis (Environmental Science and Pollution Research, 2021)

Comparative effects of dietary micro- and nano-scale chitosan on the growth performance, non-specific immunity, and resistance of silver carp Hypophthalmichthys molitrix against Staphylococcus aureus infection - Naima Younus; Amina Zuberi; Tariq Mahmoood; Wasim Akram; Muhammad Ahmad (Aquaculture International, 2020)

Population pharmacokinetics and dose optimization of ceftriaxone for children with community-acquired pneumonia - Muhammad Wasim Khan; Ya-Kun Wang; Yue-E Wu; Bo-Hao Tang; Min Kan; Hai-Yan Shi; Yi Zheng; Bao-Ping Xu; A-Dong Shen; Evelyne Jacqz-Aigrain; Li-Yuan Tian; Wei Zhao (European Journal of Clinical Pharmacology, 2020)

Correction to: Environmental efficiency and the role of energy innovation in emissions reduction - Muhammad Khalid Anser; Wasim Iqbal; Umar Suffian Ahmad; Arooj Fatima; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Single tube multiplex PCR assay for the identification of banned meat species - Memoona Iqbal; Muhammad Sulyman Saleem; Muhammad Imran; Waseem Ahmad Khan; Kamran Ashraf; M. Yasir Zahoor; Imran Rashid; Habib-Ur Rehman; Asif Nadeem; Saadat Ali; Sarwat Naz; Wasim Shehzad (Food Additives & Contaminants Part B-Surveillance, 2020)

Green remediation of saline–sodic Pb-factored soil by growing salt-tolerant rice cultivar along with soil applied inorganic amendments - Muhammad Mazhar Iqbal; Tayyaba Naz; Mazhar Iqbal Zafar; Muhammad Imtiaz; Omer Farooq; Atique ur Rehman; Shafaqat Ali; Muhammad Rizwan; Sabir Hussain; Wasim Javed; Ghulam Murtaza; Muhammad Afzal; et al. (Paddy and Water Environment, 2020)

RETRACTED ARTICLE: Trilemma assessment of energy intensity, efficiency, and environmental index: evidence from BRICS countries - Zulifqar Ali Baloch; Qingmei Tan; Nadeem Iqbal; Muhammad Mohsin; Qaiser Abbas; Wasim Iqbal; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

RETRACTED ARTICLE: Environmental efficiency and the role of energy innovation in emissions reduction - Muhammad Khalid Anser; Wasim Iqbal; Umar Suffian Ahmad; Arooj Fatima; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Characterization and synthetic biology of lipase from Bacillus amyloliquefaciens strain - Muhammad Tahir Khan; Aman Chandra Kaushik; Qurrat ul ain Rana; Shaukat Iqbal Malik; Anwar Sheed Khan; Dong-Qing Wei; Wasim Sajjad; Shabir Ahmad; Sajid Ali; Ameenullah; Muhammad Irfan (Archives of Microbiology, 2020)

Evolutionarily conserved and testis-specific gene, 4930524B15Rik, is not essential for mouse spermatogenesis and fertility - Ranjha Khan; Jingwei Ye; Ayesha Yousaf; Wasim Shah; Ayesha Aftab; Basit Shah; Qamar Zaman; Muhammad Zubair; Qinghua Shi; Xiaohua Jiang (Molecular Biology Reports, 2020)

Pigment production by cold-adapted bacteria and fungi: colorful tale of cryosphere with wide range applications - Wasim Sajjad; Ghufranud Din; Muhammad Rafiq; Awais Iqbal; Suliman Khan; Sahib Zada; Barkat Ali; Shichang Kang (Extremophiles, 2020)

Type 1 Fimbriae and Motility Play a Pivotal Role During Interactions of Salmonella typhimurium with Acanthamoeba castellanii (T4 Genotype) - Talha Mannan; Muhammad Wasim Rafique; Muhammad Haroon Bhatti; Abdul Matin; Irfan Ahmad (Current Microbiology, 2020)

Impact of urbanization, economic growth, and population size on residential carbon emissions in the SAARC countries - Muhammad Khalid Anser; Majed Alharthi; Babar Aziz; Sarah Wasim (Clean Technologies and Environmental Policy, 2020)

Assessment of nematodes in Punjab Urial (Ovis vignei punjabiensis) population in Kalabagh Game Reserve: development of a DNA barcode approach - Amna Arshad Bajwa; Jordan Patrick Cuff; Muhammad Imran; Saher Islam; Riffat Mansha; Kamran Ashraf; Arman Khan; Muhammad Imran Rashid; Muhammad Yasir Zahoor; Waseem Ahmad Khan; Habib Ur Rehman; Asif Nadeem; et al. (European Journal of Wildlife Research, 2019)

Variants in KIAA0825 underlie autosomal recessive postaxial polydactyly - Irfan Ullah; Naseebullah Kakar; Isabelle Schrauwen; Shabir Hussain; Imen Chakchouk; Khurram Liaqat; Anushree Acharya; Naveed Wasif; Regie Lyn P. Santos-Cortez; Saadullah Khan; Abdul Aziz; Kwanghyuk Lee; et al. (Human Genetics, 2019)

Molecular genetic diagnosis of Wilson disease by ARMS-PCR in a Pakistani family - Haq Nawaz Khan; Muhammad Wasim; Hina Ayesha; Fazli Rabbi Awan (Molecular Biology Reports, 2018)

Novel candidate genes and variants underlying autosomal recessive neurodevelopmental disorders with intellectual disability - Regie Lyn P. Santos-Cortez; Valeed Khan; Falak Sher Khan; Zaib-un-Nisa Mughal; Imen Chakchouk; Kwanghyuk Lee; Memoona Rasheed; Rifat Hamza; Anushree Acharya; Ehsan Ullah; Muhammad Arif Nadeem Saqib; Izoduwa Abbe; et al. (Human Genetics, 2018)

Glutamic acid assisted phyto-management of silver-contaminated soils through sunflower; physiological and biochemical response - Mujahid Farid; Shafaqat Ali; Muhammad Zubair; Rashid Saeed; Muhammad Rizwan; Rasham Sallah-Ud-Din; Ahmad Azam; Rehman Ashraf; Wasim Ashraf (Environmental Science and Pollution Research, 2018)

Factors influencing corrosion of metal pipes in soils - Muhammad Wasim; Shahrukh Shoaib; N. M. Mubarak; Inamuddin; Abdullah M. Asiri (Environmental Chemistry Letters, 2018)

Genomic and biological characterization of Newcastle disease viruses isolated from migratory mallards (Anas platyrhynchos) - Momena Habib; Tahir Yaqub; Jawad Nazir; Wasim Shehzad; Aziz-ul-Rahman; Tayyebah Sohail; Nadia Mukhtar; Arsalan Mehboob; Muhammad Munir; Muhammad Zubair Shabbir (Archives of Virology, 2018)

Development and validation of a loop-mediated isothermal amplification assay for the detection of Mycoplasma bovis in mastitic milk - Aqeela Ashraf; Muhammad Imran; Tahir Yaqub; Muhammad Tayyab; Wasim Shehzad; Claro N. Mingala; Yung-Fu Chang (Folia Microbiologica, 2018)

Aminoacidopathies: Prevalence, Etiology, Screening, and Treatment Options - Muhammad Wasim; Fazli Rabbi Awan; Haq Nawaz Khan; Abdul Tawab; Mazhar Iqbal; Hina Ayesha (Biochemical Genetics, 2018)

Ellis–van Creveld syndrome and profound deafness resulted by sequence variants in the EVC / EVC2 and TMC1 genes - Muhammad Umair; Heide Seidel; Ishtiaq Ahmed; Asmat Ullah; Tobias B. Haack; Bader Alhaddad; Abid Jan; Afzal Rafique; Tim M. Strom; Farooq Ahmad; Thomas Meitinger; Wasim Ahmad (Journal of Genetics, 2017)

Structural and functional characteristics of plant proteinase inhibitor-II (PI-II) family - Shazia Rehman; Ejaz Aziz; Wasim Akhtar; Muhammad Ilyas; Tariq Mahmood (Biotechnology Letters, 2017)

The impact of seasonal variation on organochlorine pesticide residues in buffalo and cow milk of selected dairy farms from Faisalabad region - Muhammad Wasim Sajid; Muhammad Shamoon; Muhammad Atif Randhawa; Muhammad Asim; Abdul Shakoor Chaudhry (Environmental Monitoring and Assessment, 2016)

Role of Leptin Deficiency, Inefficiency, and Leptin Receptors in Obesity - Muhammad Wasim; Fazli Rabbi Awan; Syeda Sadia Najam; Abdul Rehman Khan; Haq Nawaz Khan (Biochemical Genetics, 2016)

Mutation of ATF6 causes autosomal recessive achromatopsia - Muhammad Ansar; Regie Lyn P. Santos-Cortez; Muhammad Arif Nadeem Saqib; Fareeha Zulfiqar; Kwanghyuk Lee; Naeem Mahmood Ashraf; Ehsan Ullah; Xin Wang; Sundus Sajid; Falak Sher Khan; Muhammad Amin-ud-Din; Joshua D. Smith; et al. (Human Genetics, 2015)

Missense mutations (p.H371Y, p.D438Y) in gene CHEK2 are associated with breast cancer risk in women of Balochistan origin - Abdul Hameed Baloch; Shakeela Daud; Nafeesa Raheem; Muhammad Luqman; Adeel Ahmad; Abdul Rehman; Jameela Shuja; Saeeda Rasheed; Akhtar Ali; Naseebullah Kakar; Hafiz Khush Naseeb; Mohammad Alam Mengal; et al. (Molecular Biology Reports, 2014)

A novel WDR62 mutation causes primary microcephaly in a Pakistani family - Mazhar Mustafa Memon; Syed Irfan Raza; Sulman Basit; Rizwana Kousar; Wasim Ahmad; Muhammad Ansar (Molecular Biology Reports, 2013)

Problems encountered in bicistronic IRES-GFP expression vectors employed in functional analyses of GC-induced genes - Muhammad Mansha; Muhammad Wasim; Christian Ploner; Abrar Hussain; Asma Abdul Latif; Muhammad Tariq; Anita Kofler (Molecular Biology Reports, 2012)

Molecular phylogeny of Pakistani riverine buffalo based on genetic variability of mitochondrial cytochrome b gene - Rashid Saif; Muhammad Wasim; Masroor Ellahi Babar (Molecular Biology Reports, 2012)

Elemental contamination in urban parks of Rawalpindi/Islamabad—a source identification and pollution level assessment study - Sajid Iqbal; Mohammad Wasim; Muhammad Tufail; Mohammad Arif; Muhammad M. Chaudhry (Environmental Monitoring and Assessment, 2012)

Expression and glucocorticoid-regulation of “Bam”, a novel BH3-only transcript in acute lymphoblastic leukemia - Muhammad Mansha; Muhammad Wasim; Anita Kofler; Christian Ploner (Molecular Biology Reports, 2012)

Carnivore diet analysis based on next‐generation sequencing: application to the leopard cat ( Prionailurus bengalensis ) in Pakistan - WASIM SHEHZAD; TIAYYBA RIAZ; MUHAMMAD A. NAWAZ; CHRISTIAN MIQUEL; CAROLE POILLOT; SAFDAR A. SHAH; FRANÇOIS POMPANON; ERIC COISSAC; PIERRE TABERLET (Molecular Ecology, 2012)
Diet analysis is a prerequisite to fully understand the biology of a species and the functioning of ecosystems. For carnivores, traditional diet analyses mostly rely upon the morphological identification of undigested remains in the faeces. Here, we developed a methodology for carnivore diet analyses based on the next‐generation sequencing. We applied this approach to the analysis of the vertebrate component of leopard cat diet in two ecologically distinct regions in northern Pakistan. Despite being a relatively common species with a wide distribution in Asia, little is known about this elusive predator. We analysed a total of 38 leopard cat faeces. After a classical DNA extraction, the DNA extracts were amplified using primers for vertebrates targeting about 100 bp of the mitochondrial 12S rRNA gene, with and without a blocking oligonucleotide specific to the predator sequence. The amplification products were then sequenced on a next‐generation sequencer. We identified a total of 18 prey taxa, including eight mammals, eight birds, one amphibian and one fish. In general, our results confirmed that the leopard cat has a very eclectic diet and feeds mainly on rodents and particularly on the Muridae family. The DNA‐based approach we propose here represents a valuable complement to current conventional methods. It can be applied to other carnivore species with only a slight adjustment relating to the design of the blocking oligonucleotide. It is robust and simple to implement and allows the possibility of very large‐scale analyses.

Genetic mapping of an autosomal recessive postaxial polydactyly type A to chromosome 13q13.3–q21.2 and screening of the candidate genes - Umm-e-Kalsoom; Sulman Basit; Syed Kamran-ul-Hassan Naqvi; Muhammad Ansar; Wasim Ahmad (Human Genetics, 2012)

Novel mutations in the keratin-74 (KRT74) gene underlie autosomal dominant woolly hair/hypotrichosis in Pakistani families - Naveed Wasif; Syed Kamran ul-Hassan Naqvi; Sulman Basit; Nadir Ali; Muhammad Ansar; Wasim Ahmad (Human Genetics, 2011)

DFNB89, a novel autosomal recessive nonsyndromic hearing impairment locus on chromosome 16q21-q23.2 - Sulman Basit; Kwanghyuk Lee; Rabia Habib; Leon Chen; Umm-e-Kalsoom; Regie Lyn P. Santos-Cortez; Zahid Azeem; Paula Andrade; Muhammad Ansar; Wasim Ahmad; Suzanne M. Leal (Human Genetics, 2011)

Genetic mapping of a novel hypotrichosis locus to chromosome 7p21.3–p22.3 in a Pakistani family and screening of the candidate genes - Sulman Basit; Ghazanfar Ali; Naveed Wasif; Muhammad Ansar; Wasim Ahmad (Human Genetics, 2010)

In Vitro Distribution of Gold in Serum Proteins after Incubation of Sodium Aurothiomalate and Auranofin with Human Blood and its Pharmacological Significance - Mohammad S. Iqbal; Syed G. Taqi; Muhammad Arif; Muhammad Wasim; Muhammad Sher (Biological Trace Element Research, 2009)

Ectodermal dysplasia-cutaneous syndactyly syndrome maps to chromosome 7p21.1-p14.3 - Muhammad Tariq; Muhammad Nasim Khan; Wasim Ahmad (Human Genetics, 2009)

Novel mutations in G protein-coupled receptor gene (P2RY5) in families with autosomal recessive hypotrichosis (LAH3) - Zahid Azeem; Musharraf Jelani; Gul Naz; Muhammad Tariq; Naveed Wasif; Syed Kamran-ul-Hassan Naqvi; Muhammad Ayub; Masoom Yasinzai; Muhammad Amin-ud-din; Abdul Wali; Ghazanfar Ali; Muhammad Salman Chishti; et al. (Human Genetics, 2008)

A syndromic form of autosomal recessive congenital microcephaly (Jawad syndrome) maps to chromosome 18p11.22–q11.2 - Muhammad Jawad Hassan; Muhammad Salman Chishti; Syed Muhammad Jamal; Muhammad Tariq; Wasim Ahmad (Human Genetics, 2008)

A mutation in the lipase H (LIPH) gene underlie autosomal recessive hypotrichosis - Ghazanfar Ali; Muhammad Salman Chishti; Syed Irfan Raza; Peter John; Wasim Ahmad (Human Genetics, 2007)

DFNB68, a novel autosomal recessive non-syndromic hearing impairment locus at chromosomal region 19p13.2 - Regie Lyn P. Santos; Muhammad Jawad Hassan; Shaheen Sikandar; Kwanghyuk Lee; Ghazanfar Ali; Protacio E. Martin; Michael Angelo L. Wambangco; Wasim Ahmad; Suzanne M. Leal (Human Genetics, 2006)

Localization of a novel autosomal recessive nonsyndromic hearing impairment locus DFNB65 to chromosome 20q13.2–q13.32 - Aamira Tariq; Regie Lyn P. Santos; Mohammad Nasim Khan; Kwanghyuk Lee; Muhammad Jawad Hassan; Wasim Ahmad; Suzanne M. Leal (Journal of Molecular Medicine, 2006)

Localization of a novel locus for alopecia with mental retardation syndrome to chromosome 3q26.33–q27.3 - Peter John; Ghazanfar Ali; Muhammad S. Chishti; Syed Muhammad S. Naqvi; Suzanne M. Leal; Wasim Ahmad (Human Genetics, 2006)

A novel autosomal recessive non-syndromic hearing impairment locus (DFNB47) maps to chromosome 2p25.1-p24.3 - Muhammad Jawad Hassan; Regie Lyn P. Santos; Muhammad Arshad Rafiq; Maria H. Chahrour; Thanh L. Pham; Muhammad Wajid; Nadine Hijab; Michael Wambangco; Kwanghyuk Lee; Muhammad Ansar; Kai Yan; Wasim Ahmad; et al. (Human Genetics, 2006)